A Policy Implementation Model in Decentralised Governance: Human Development in West Bandung Regency - Yusca, Azis Zulficar Aly; Achmad, Mansyur; Tahir, Irwan; Masrich, Andi (Jurnal Manajemen Pelayanan Publik, 2025)
Regional division as a decentralisation strategy in Indonesia has created new autonomous regions (DOB) with the hope of improving public services and community welfare, including human development. However, in practice, many DOBs have lagged behind in achieving the Human Development Index (HDI). This study aims to analyse the implementation of regional division policies in improving the HDI in West Bandung Regency, using the modified Van Meter and Van Horn model with the addition of a leadership dimension. The study employs a qualitative approach with a case study method, data collection through in-depth interviews, document analysis, and participatory observation. The findings reveal that the implementation of policies in KBB still faces various challenges, such as the lack of alignment between policy objectives and regional performance indicators, resource constraints, bureaucratic fragmentation, and weak capacity and motivation among implementing agents. The addition of the leadership element has proven to be a crucial variable in bridging the gap between central policies and local realities, as well as enhancing the effectiveness of cross-institutional coordination and communication. These findings contribute to the development of policy implementation theory by expanding the classical analytical framework. This research is relevant for policymakers, particularly in designing more adaptive, responsive, and context-based local policy implementation strategies.